2008
DOI: 10.1016/j.expneurol.2007.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of striatal glutamate transmission in rotenone-treated mice: MRI/MRS in vivo studies

Abstract: Animal models treated with agricultural chemicals, such as rotenone, reproduce several degenerative features of human central nervous system (CNS) diseases. Glutamate is the most abundant excitatory amino acid transmitter in the mammalian central nervous system and its transmission is implicated in a variety of brain functions including mental behavior and memory. Dysfunction of glutamate neurotransmission in the CNS has been associated with a number of human neurodegenerative diseases, either as a primary or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…It is clear from the present study that CPF exerts an imbalance in neuro-chemical homeostasis resulting in AChE inhibition (Tables 1, 2, 3, 4). The inhibition of AChE activity disturbs the metabolic and neuronal activities and also causes deformities of cell membrane (Moussa et al 2008). Decreased AChE activity observed following CPF exposure in the present study is in agreement with the earlier report (Moussa et al 2008), while decreased ChAT activity levels in this study on exposure to CPF could be related to changes in high affinity of choline uptake as a result of oxidative stress.…”
Section: Influence Of Age and Regionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is clear from the present study that CPF exerts an imbalance in neuro-chemical homeostasis resulting in AChE inhibition (Tables 1, 2, 3, 4). The inhibition of AChE activity disturbs the metabolic and neuronal activities and also causes deformities of cell membrane (Moussa et al 2008). Decreased AChE activity observed following CPF exposure in the present study is in agreement with the earlier report (Moussa et al 2008), while decreased ChAT activity levels in this study on exposure to CPF could be related to changes in high affinity of choline uptake as a result of oxidative stress.…”
Section: Influence Of Age and Regionsupporting
confidence: 93%
“…Activity of AChE is vital for the functioning of cholinergic system and represents a prime target on which some toxicants can exert a detrimental effect (Moussa et al 2008). Similarly, ChAT activity provides insight into the potential rate of ACh biosynthesis and is often used as a prototypical marker for functional cholinergic neurons (Moussa et al 2008). It is clear from the present study that CPF exerts an imbalance in neuro-chemical homeostasis resulting in AChE inhibition (Tables 1, 2, 3, 4).…”
Section: Influence Of Age and Regionmentioning
confidence: 72%
See 2 more Smart Citations
“…It has been suggested that salsolinol leads to neurotoxicity through inhibition of mitochondrial complex II (succinate-Q reductase) activity, and/or by initiating apoptotic processes by generating free radicals (Maruyama et al, 1995, Storch et al, 2000). Rotenone’s effect has been attributed to inhibition of mitochondrial complex I (Betarbet et al, 2000, Alam and Schmidt, 2002, Hoglinger et al, 2003), the release of NADPH oxidase-derived superoxide from activated microglia (Gao et al, 2002) and possibly alteration of glutamate transmission (Leng et al, 2003, Moussa et al, 2008). Both drugs might also cause inflammation, which appears to contribute to the formation of PD (Gao et al, 2003a,b, Zhang et al, 2011, Chinta et al, 2013).…”
Section: Discussionmentioning
confidence: 99%